Mental Health Impact of COVID-19 Pandemic on Health Care Workers in Ebonyi State, Southeast, Nigeria - Anozie, Okechukwu B.; Nwafor, Johnbosco I.; Nwokporo, Ephraim I.; Esike, Chidi U.; Ewah, Richard L.; Eze, Justus N.; Azuogu, Benedict N.; Ukaegbe, Chukwuemeka I. (International Journal of Innovative Research in Medical Science, 2020)
Background: Globally, mental health issues have become one of the predominant public health concerns as a result of the COVID-19 outbreak. The impact of COVID-19 pandemic on the mental health of frontline healthcare workers has not been fully described in Nigeria. Aim: To determine the mental health impact of COVID-19 pandemic and its associated factors among frontline healthcare workers in Ebonyi State, Nigeria. Materials and methods: This was an online cross-sectional study conducted among 315 frontline healthcare workers treating COVID-19 patients at Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Ebonyi State, Nigeria. The mental health outcome of the participants was assessed using the short form of the Mental Health Continuum (MHC-SF). Results: The prevalence of mental health outcome for different categories was 47% (n = 148) for flourishing, 28.3% (n = 89) for moderate and 24.7% (n = 78) for languishing mental health. The predictors of languishing mental health outcome were being married (OR = 3.12, 95%CI 1.67 - 4.09, p = 0.035), a physician (OR = 4.09, 95%CI 1.98 - 5.61, p = 0.002), a nurse (OR = 2.21, 95%CI 0.05 - 0.24, p < 0.001), limited access to personal protective equipment (OR = 3.25, 95%CI 1.62 - 6.22, p = 0.043) and self-isolation and quarantine due to SARS-CoV-2 infection (OR = 3.03, 95%CI 0.02 - 0.95, p < 0.001). Conclusion: Nigeria’s frontline healthcare workers, especially physicians and nurses, are experiencing COVID-19 related psychological distress. There is need to develop and implement interventions to reduce the impact of prolonged psychological distress on long-term mental wellbeing in healthcare workers treating COVID-19 patients.